Near-Infrared Activation of Sensory Rhodopsin II Mediated by NIR-to-Blue Upconversion Nanoparticles - Yaguchi, Momo; Jia, Xiaodan; Schlesinger, Ramona; Jiang, Xiue; Ataka, Kenichi; Heberle, Joachim (Frontiers in Molecular Biosciences, 2022)
Direct optical activation of microbial rhodopsins in deep biological tissue suffers from ineffective light delivery because visible light is strongly scattered and absorbed. NIR light has deeper tissue penetration, but NIR-activation requires a transducer that converts NIR light into visible light in proximity to proteins of interest. Lanthanide-doped upconversion nanoparticles (UCNPs) are ideal transducer as they absorb near-infrared (NIR) light and emit visible light. Therefore, UCNP-assisted excitation of microbial rhodopsins with NIR light has been intensively studied by electrophysiology technique. While electrophysiology is a powerful method to test the functional performance of microbial rhodopsins, conformational changes associated with the NIR light illumination in the presence of UCNPs remain poorly understood. Since UCNPs generally have multiple emission peaks at difference wavelengths, it is important to reveal if UCNP-generated visible light induces similar structural changes of microbial rhodopsins as conventional visible light illumination does. Here, we synthesize the lanthanide-doped UCNPs that convert NIR light to blue light. Using these NIR-to-blue UCNPs, we monitor the NIR-triggered conformational changes in sensory rhodopsin II from Natronomonas pharaonis (NpSRII), blue light-sensitive microbial rhodospsin, by FTIR spectroscopy. FTIR difference spectrum of NpSRII was recorded under two different excitation conditions: (ⅰ) with conventional blue light, (ⅱ) with UCNP-generated blue light upon NIR excitation. Both spectra display similar spectral features characteristic of the long-lived M photointermediate during the photocycle of NpSRII. This study demonstrates that NIR-activation of NpSRII mediated by UCNPs takes place in a similar way to direct blue light activation of NpSRII.